2020
DOI: 10.1111/jocd.13756
|View full text |Cite
|
Sign up to set email alerts
|

Postinflammatory and rebound hyperpigmentation as a complication after treatment efficacy of telangiectatic melasma with 585 nanometers Q‐switched Nd: YAG laser and 4% hydroquinone cream in skin phototypes III‐V

Abstract: Background:The potential efficacy of vascular component-targeted laser has been evaluated for the treatment of melasma, which commonly found with the co-existence of telangiectasia. Aims:To evaluate the treatment efficacy and safety of 585-nm QSNYL and 4% HQ cream combination vs 4% HQ cream alone for telangiectatic melasma in the skin phototypes III-V.Patients/Methods: Twenty-one Thai female patients with telangiectatic melasma and Fitzpatrick skin phototypes (FPTs) III-V were randomly treated with the 585-nm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…9 A combination treatment of YAG laser and hydroquinone cream, whilst showing good efficacy and skin rejuvenation effects for telangiectatic melasma, should be used cautiously in individuals with FPT IV-V to avoid laser-induced pigment alteration, PIH and rebound hyperpigmentation. 22,23 It is recommended to perform a test before doing the complete procedure. A long pulse duration coagulates the target without bursting the vessels and the vessels often disappear after the first laser pass leaving erythema and oedema.…”
Section: Ablative Fractional Resurfacing Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…9 A combination treatment of YAG laser and hydroquinone cream, whilst showing good efficacy and skin rejuvenation effects for telangiectatic melasma, should be used cautiously in individuals with FPT IV-V to avoid laser-induced pigment alteration, PIH and rebound hyperpigmentation. 22,23 It is recommended to perform a test before doing the complete procedure. A long pulse duration coagulates the target without bursting the vessels and the vessels often disappear after the first laser pass leaving erythema and oedema.…”
Section: Ablative Fractional Resurfacing Techniquesmentioning
confidence: 99%
“…Combining topical therapy with procedures such as chemical peels, IPL, fractional non‐ablative lasers or radiofrequency, pigment lasers (microsecond, picosecond, Q‐switched) and microneedling, may be required to treat melasma and PIH 9 . A combination treatment of YAG laser and hydroquinone cream, whilst showing good efficacy and skin rejuvenation effects for telangiectatic melasma, should be used cautiously in individuals with FPT IV‐V to avoid laser‐induced pigment alteration, PIH and rebound hyperpigmentation 22,23 . It is recommended to perform a test before doing the complete procedure.…”
Section: Part 1: Non‐surgical Proceduresmentioning
confidence: 99%
“…9,10 HQ (2%-4%) is widely prescribed for treating hyperpigmentation. Lueangarun et al 11 assessed the treatment efficacy and safety of 585 nm Q-switched neodymium-doped yttrium aluminium garnet (Nd:YAG) laser treatment combined with 4% HQ cream versus 4% HQ cream alone for telangiectatic melasma in 21 patients from Thailand. They observed a high incidence of PIH and rebound hyperpigmentation in patients with darker Fitzpatrick skin phototypes receiving Q-switched Nd:YAG laser treatment and 4% HQ cream, indicating the potential risk of this treatment regimen.…”
Section: Cosmetic Lasersmentioning
confidence: 99%
“…Studies have shown that melasma is associated with a poor Quality of Life (QOL) in some affected individuals [20][21][22]. Although there is a wide variety of treatment interventions, the suitability of these treatment modalities is limited due to their negative side effects, particularly in people with darker skin [23][24][25][26], hence there is a necessity to investigate more treatment interventions that will be both safe and effective for all skin types. Tyrosinase inhibitors are extensively used as complexion modifiers in the cosmetic industry [27].…”
Section: Introductionmentioning
confidence: 99%